Efficacy of low carbohydrate and ketogenic diets in treating mood and anxiety disorders: systematic review and implications for clinical practice. Issue 3 (17th May 2023) - Dietch, Daniel M.; Kerr-Gaffney, Jess; Hockey, Meghan; Marx, Wolfgang; Ruusunen, Anu; Young, Allan H.; Berk, Michael; Mondelli, Valeria
Abstract : Background: There is mounting interest in the potential efficacy of low carbohydrate and very low carbohydrate ketogenic diets in various neurological and psychiatric disorders. Aims: To conduct a systematic review and narrative synthesis of low carbohydrate and ketogenic diets (LC/KD) in adults with mood and anxiety disorders. Method: MEDLINE, Embase, PsycINFO and Cochrane databases were systematically searched for articles from inception to 6 September 2022. Studies that included adults with any mood or anxiety disorder treated with a low carbohydrate or ketogenic intervention, reporting effects on mood or anxiety symptoms were eligible for inclusion. PROSPERO registration CRD42019116367. Results: The search yielded 1377 articles, of which 48 were assessed for full-text eligibility. Twelve heterogeneous studies (stated as ketogenic interventions, albeit with incomplete carbohydrate reporting and measurements of ketosis; diet duration: 2 weeks to 3 years; n = 389; age range 19 to 75 years) were included in the final analysis. This included nine case reports, two cohort studies and one observational study. Data quality was variable, with no high-quality evidence identified. Efficacy, adverse effects and discontinuation rates were not systematically reported. There was some evidence for efficacy of ketogenic diets in those with bipolar disorder, schizoaffective disorder and possibly unipolar depression/anxiety. Relapse after discontinuation of the diet was reported in some individuals. Conclusions: Although there is no high-quality evidence of LC/KD efficacy in mood or anxiety disorders, several uncontrolled studies suggest possible beneficial effects. Robust studies are now needed to demonstrate efficacy, to identify clinical groups who may benefit and whether a ketogenic diet (beyond low carbohydrate) is required and to characterise adverse effects and the risk of relapse after diet discontinuation.